Предмет: Алгебра,
автор: alhimik9991
Помогите пожалуйста =((
Приложения:
![](https://files.topotvet.com/i/3e5/3e5d59744aa4f53d32263b5f97e3d943.png)
Ответы
Автор ответа:
0
вариант второй. я так думаю
Автор ответа:
0
Правильный ответ 2,
Потому что по формуле a^2-b^2=(a+b)(a-b)
(√12-√27)(√12+√27)=√12^2-√27^2=12-27=-15
Потому что по формуле a^2-b^2=(a+b)(a-b)
(√12-√27)(√12+√27)=√12^2-√27^2=12-27=-15
Похожие вопросы
Предмет: Право,
автор: savelijmineev5
Предмет: Биология,
автор: iegor3391
Предмет: Математика,
автор: d61851454
Предмет: Математика,
автор: verontim04
Предмет: Биология,
автор: goshabaykov